Interrelations of physical state parameters and biological age of students in the process of physical education - Oleksandr Pryimakov; Marek Sawczuk; Stanislav Prysiazhniuk; Nataliya Mazurok; Oleksandr Petrachkov (Physical Education of Students)
Background and Study Aim. The objective of the study is to investigate the relationships of students' biological age (BA) with the parameters of functional and physical fitness (PF) in the process of adaptation to standard (university) and experimental physical education programs.